Kafā’ah dalam Perspektif Hadis Tunkahu al-Mar’atu li Arba’: Telaah Kriteria Pemilihan Pasangan dalam Islam - Safriani, Laela; Ilyas, Abustani; Bahri, Alim (JISH: Jurnal Ilmu Syariah dan Hukum, 2026)
Kafā’ah is one of the essential principles in Islamic marriage, functioning to maintain harmony and sustainability within the family. The hadith Tunkahu al-Mar’atu li Arba’, which explains four criteria for choosing a spouse-wealth, lineage, beauty, and religiosity-serves as a normative foundation for understanding this concept. This article aims to analyze the concept of kafā’ah from the perspective of the hadith Tunkahu al-Mar’atu li Arba’ and to examine the criteria for spouse selection in Islam based on scholarly interpretations. This study employs a qualitative method with a library research approach, utilizing data sources such as hadith collections, classical and contemporary Islamic scholarship, and relevant academic journal articles. Data analysis is conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the hadith Tunkahu al-Mar’atu li Arba’ is not intended to legitimize spouse selection based solely on material or outward aspects, but rather to describe human tendencies in choosing a partner. Scholars emphasize that religiosity is the most fundamental and decisive element of kafā’ah, while wealth, lineage, and beauty function as supporting factors. Therefore, the concept of kafā’ah in this hadith highlights the importance of balancing spiritual and social aspects in selecting a life partner to achieve a harmonious family grounded in Islamic values